Implementation Of The Use Of Artificial Intelligence In Higher Education - Abigail Leffia; Alexander Chou Kiboyi; Rizky Fredrin Terizla (Blockchain Frontier Technology, 2024)
Higher education is currently undergoing significant digital transformation, with artificial intelligence (AI) emerging as a key innovation shaping this change. This research elaborates on the implementation and impact of AI in the context of higher education. The discussion encompasses the influence of AI on the learning process, improvements in administrative efficiency, and shifts in the education paradigm. The research also explores specific AI applications, such as adaptive learning, sentiment analysis, and data management, which substantially enrich student learning experiences and support decision-making in higher education institutions. While the benefits are substantial, the research also highlights challenges and issues that may arise, including privacy concerns, data security, and the integration of technology into academic curricula. In conclusion, the implementation of artificial intelligence in higher education has the potential to be a cornerstone in shaping students who are prepared for the demands of knowledge-based societies and contributing to the development of a more adaptive and innovative education system.